Sintesis Karbon Aktif Kulit Durian Serta Penyerapannya Terhadap Logam Berat Pb(II) dengan Metode Batch - Devi Lestari; Edi Nasra (Departemen Kimia FMIPA UNP, 2022)
Activated carbon from durian peel is synthesized by chemical activation using an alkaline sodium hydroxide. The carbonization process is carried out for 2 hours at a temperature of 320ºC. Activated carbon is characterized by conducting several quality tests based on SNI 06-3730-1995 which has met all specified standards. The results of the FTIR spectrum show that activated carbon has a cluster of -OH at wave numbers 3000-3400 cm-1, C = C at wave numbers 1540-1630 cm-1, C-O in wave numbers 1150-1275 cm-1. Adsorption test results by batch method showed that the prepared activated carbon was able to absorb Pb2+ ions at an optimum concentration of 280 mg/L and an optimum contact time of 150 minutes with an absorption capacity of 34,145 mg/g that was close to langmuir's isoterm equation by producing a regression coefficient value of R2 = 0.999.